A Novel Imprinted Electrochemical Sensor for Dopamine Determination Based on Electron Conductivity Enhanced by Ferrocenyl Chalcone Derivative Film (Journal of Atomic and Molecular Sciences, 2019)
A novel biochemical sensor based on molecular imprinted technology was built throughelectropolymerization. One of the keystones of the technology is the discovery and application of newconductive polymer. Herein, a new conductive ferrocenyl chalcone derivative: [1-Oxo-3-(3-thienyl)-2-propen-1-yl] ferrocene (OTPylFc) was synthesized and characterized by nuclear magnetic resonance (NMR) andfinally adopted in the technology. The OTPylFc and pyrrole mixture was eletropolymerized in this work andshowed satisfying result in improving current peaks. The linear relationship was 1.729× 10$^{-6}$ M to 6.916 × 10$^{-4}$ M. It is believed that the structure and their conductive analogs formed co-polymers would have a promisingprospect in future research.